Thermal annealing in silicon photonics ring modulators. (1st March 2023) - Lalović, M.; Detraz, S.; Marcon, L.; Olanterä, L.; Prousalidi, T.; Sandven, U.; Scarcella, C.; Sigaud, C.; Soós, C.; Troska, J.
Abstract: Silicon photonics technology promises significant improvements for fibre optic links of future upgrades of HEP experiments. Such systems will require high levels of radiation tolerance and silicon photonics modulators have been shown to be very robust when exposed to high levels of radiation under certain conditions. We demonstrate for the first time that changing the temperature of ring modulators during or after irradiation can significantly improve their performance.